Islamic Sukuk: Pricing Mechanism and Rating - Ahmed, Essia Ries; Islam, Md. Aminul; Alabdullah, Tariq Tawfeeq Yousif (Journal of Asian Scientific Research, 2014)
The advantage of sukuk is that they are compliant with shariah principles. Sukuk are therefore attractive investment instruments for Islamic financial institutions, shariah managed funds and takaful Islamic insurance companies that cannot invest in conventional securities that involve payment of interest or riba. As well as there are an increasing number of Muslims of high net worth who want their asset holdings to comply with shariah rules. The main objective of this paper is to elucidate and describe the significance of the pricing mechanisms and rating on Islamic sukuk.